Online Frequency Distribution Application Using a Javascript-Based Blogger Platform - Rhomdani, Rohmad Wahid; Galatea, Chusnul Khotimah (Indonesian Journal of Education and Mathematical Science, 2024)
This research develops an online frequency distribution application using the Javascript-based Blogger platform. The method used is a literature study, namely examining the frequency distribution of both the formulas used and descriptions in the Javascript programming language using mathematical logic. Online frequency distributions are essential for analyzing data, and by utilizing Javascript capabilities, this application allows users to easily input data and automatically generate informative frequency distributions. This article will discuss the technical implementation, including the use of the Javascript programming language and its integration with the Blogger platform for online content creation. The results of this research contribute to the development of statistical applications that are easy to use and access online, thereby helping users understand and analyze their data more effectively.